Pheochromocytoma and Paraganglioma: Current Functional and Future Molecular Imaging - Blanchet, Elise M.; Martucci, Victoria; Pacak, Karel (Frontiers in Oncology, 2012)
Paragangliomas are neural crest-derived tumors, arising either from chromaffin sympathetic tissue (in adrenal, abdominal, intra-pelvic, or thoracic paraganglia) or from parasympathetic tissue (in head and neck paraganglia). They have a specific cellular metabolism, with the ability to synthesize, store, and secrete catecholamines (although most head and neck paragangliomas do not secrete any catecholamines). This disease is rare and also very heterogeneous, with various presentations (e.g., in regards to localization, multifocality, potential to metastasize, biochemical phenotype, and genetic background). With growing knowledge, notably about the pathophysiology and genetic background, guidelines are evolving rapidly. In this context, functional imaging is a challenge for the management of paragangliomas. Nuclear imaging has been used for exploring paragangliomas for the last three decades, with MIBG historically as the first-line exam. Tracers used in paragangliomas can be grouped in three different categories. Agents that specifically target catecholamine synthesis, storage, and secretion pathways include: 123 and 131I-metaiodobenzylguanidine (123/131I-MIBG), 18F-fluorodopamine (18F-FDA), and 18F-fluorodihydroxyphenylalanine (18F-FDOPA). Agents that bind somatostatin receptors include 111In-pentetreotide and 68Ga-labeled somatostatin analog peptides (68Ga-DOTA-TOC, 68Ga-DOTA-NOC, 68Ga-DOTA-TATE). The non-specific agent most commonly used in paragangliomas is 18F-fluorodeoxyglucose (18F-FDG). This review will first describe conventional scintigraphic exams that are used for imaging paragangliomas. In the second part we will emphasize the interest in new PET approaches (specific and non-specific), considering the growing knowledge about genetic background and pathophysiology, with the aim of understanding how tumors behave, and optimally adjusting imaging technique for each tumor type.